The Influence of Dance on Social Skills - Kovač, Maja (Širjenje obzorij o poučevanju glasbe, 2025)
The aim of this paper is to examine the effects of dance on the development of social skills across different age groups. Dance, as a form of artistic expression and physical activity, can enhance communication skills, boost self-confidence, and foster empathy and interpersonal relationships. Studies indicate that most participants report an improved ability to express emotions following dance programmes. Additionally, research participants have reported increased self-confidence and a heightened sense of connectedness with others. These findings support the conclusion that dance significantly contributes to enhancing social dynamics and improving quality of life.